2006
DOI: 10.1111/j.1365-2109.2005.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the trophic structure in organically fertilized and feed-driven tilapia culture environments using multivariate analyses

Abstract: Reports of similar yields in manure and feed-driven tilapia culture environments raise questions on food utilization in these environments. The possibility that similar production rates are because of utilization of di¡erent foods was investigated using exploratory techniques of multivariate analyses. Using factor analysis, trophic pathways through which food becomes available to ¢sh were explored, and using ANOVA models, water quality, sediment quality and tilapia growth and yields were compared. Conceptual g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Under traditional pond management, other fish species than grass carp also assimilated nitrogen from natural food resources. Especially high enrichments in 15 N were observed for Nile tilapia under traditional pond management which showed the strong dependency of Nile tilapia on a wide range of natural food resources as reported by many researchers (Beveridge et al 1989;Dempster et al 1993;Muendo et al 2006). Mrigal, known to be a bottom feeder on zoobenthos (Milstein et al 2002), also showed higher enrichments of the tracer within the first 15 days after tracer application.…”
Section: Tracer Uptake In the Fish Speciesmentioning
confidence: 60%
“…Under traditional pond management, other fish species than grass carp also assimilated nitrogen from natural food resources. Especially high enrichments in 15 N were observed for Nile tilapia under traditional pond management which showed the strong dependency of Nile tilapia on a wide range of natural food resources as reported by many researchers (Beveridge et al 1989;Dempster et al 1993;Muendo et al 2006). Mrigal, known to be a bottom feeder on zoobenthos (Milstein et al 2002), also showed higher enrichments of the tracer within the first 15 days after tracer application.…”
Section: Tracer Uptake In the Fish Speciesmentioning
confidence: 60%
“…Most of the soil parameter values except organic carbon were higher at harvest compared with initial. It occurred mainly by the accumulation of nutrients from metabolites and feeds in the sediments (Islam, Sarker, Yamamoto, Wahab & Tanaka ; Muendo, Milstein, van Dam, Gamal, Stoorvogel & Verdegem ) and the incidence was supported by Avnimelech and Ritvo () who reported that cultured aquatic animals may contain between 5% and 40% of nutrients in the feed (carbon, nitrogen, phosphorus) and the rest is accumulated in pond sediments. Significantly higher amount of soil phosphorus and nitrogen contents in the higher density treatments compared with those in the lowest density indicated more accumulation of nutrients in presence of greater number of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Unsuitable water quality elements such as water temperature (Sifa et al 2002;Cagauan 2001;Black 1998;Alcaraz et al 1993;Chervinski 1982), water oxygen (Black 1998;Ross 2000) and water pH (Svobodova et al 1993) levels were shown to have a negative effect on fish growth. Especially within extensive and semi-intensive aquaculture systems, fish growth is correlated with the availability and abundance of natural food resources (Rahman et al 2008b;Muendo et al 2006;Schroeder et al 1990;Spataru et al 1983;Kolar and Rahel 1993;Pucher et al 2011b), and both water quality and the availability of natural food are primarily or secondarily affected by the suspended particle load. During the research in Yen Chau district, ponds with maize and cassava fields on yellow soils in the watershed above and fed by rain water, showed a distinctly higher suspended solids load than ponds located on the rice paddy plateaus and fed by reservoir water.…”
Section: Evaluation Of Implemented Modifications In the Pond Managemementioning
confidence: 99%